How to run a sustainability science research group sustainably? - Tobias Plieninger; Nora Fagerholm; Claudia Bieling (SPRINGER JAPAN KK, 2022)
Rigorous sustainability science includes addressing pressing real-world problems, weaving multiple knowledge systems, and striving for transformative change. However, these key attributes of sustainability science often conflict with university structures and established academic work practices, for instance with regard to frequent long-distance travel. Such contradictions between key principles of sustainability and everyday practices are experienced by many researchers not only at university level, but also in their individual behaviors. To help resolve this widespread divergence, we present ten principles to foster the sustainability of a research group working in sustainability science, based on our personal experiences and experiments as research group leaders. These principles comprise: (1) monitor the environmental footprint, (2) foster learning and innovation, (3) reduce the environmental footprint, (4) nurture campus sustainability, (5) embrace sustainability in private life, (6) constructively deal with environmental anxiety, (7) design research projects for sustainability impact, (8) engage with stakeholders, (9) capitalize on sustainability teaching, and (10) recognize biases and limits. Applying sustainability principles in everyday research practices can provide important social tipping points that may trigger the spreading of new social norms and behaviors.